Jesintel : living wisdom from Coast Salish elders - Hillaire, Darrell; Frey, Natasha; Garreau, Beau; Mapes, Lynda, 1959-; Brown, Nicole; Washington, Danita (University of Washington Press, 2023)
"Dynamic and diverse, Coast Salish culture is bound together by shared values and relations that generate a resilient worldview. Jesintel-"to learn and grow together"-characterizes the spirit of this book, which brings the cultural teachings of nineteen elders to new generations. Featuring interviews that share powerful experiences and stories, Jesintel illuminates the importance of ethical reciprocal relationships and the interconnectedness of places, land, water, and the spirit within all things. Elders offer their perspectives on language revitalization, Coast Salish family values and naming practices, salmon, sovereignty, canoe racing, and storytelling. They also share traumatic memories, including of their boarding school experiences and the epidemics that ravished their communities. Jesintel highlights the importance of maintaining relations and traditions in the face of ongoing struggles. Collaboration is at the heart of this work and informs how the editors and community came together to honor the boundless relations of Coast Salish people and their territories"--